Comparing image perception of bladder tumors in four different Storz Professional Image Enhancement System modalities using the íSPIES app - Kamphuis, Guido M.; Knoll, Thomas (Journal of endourology, 2016)
Objectives: To evaluate the variation of interpretation of the same bladder urothelium image in different Storz Professional Image Enhancement System (SPIES) modalities. SPIES contains a White light (WL), Spectra A (SA), Spectra B (SB), and Clara and Chroma combined (CC) modality.Materials and Methods: An App for the iPAD retina was developed to study evaluation of images. A total of 80 images from 20 bladder areas acquired in four modalities were included. Seventy-three participants completed the study. Images were analyzed on differences in delineated tumor margin variation, perceived quality of the image, and delineation time.Results: A separation between high agreement (n = 14) and low agreement (n = 6) images was found. In high agreement images, no difference in root mean square (RMS) was found between modalities. In low agreement images, WL (26.5 pixels) and SA (33.4 pixels) had a higher RMS than CC (18 pixels) and SB (21.4 pixels). The quality of SPIES modalities images was rated significantly higher. Delineation time was similar.Conclusion: In low agreement cases, images in CC and SB have less variation in interpretation than WL and SA. The image quality in SPIES modalities is graded significantly higher than WL. There is no difference in delineation time between modalities.
Gesehen am 25.11.2019